Impact of an Educational Program Based on the Van Hiele Model on the Achievement in Contemporary Arts among Students of the Fine Arts Education Department (Journal of the College of Basic Education, 2025)
The current researcher aimed to identify the effect of an educational program to create a Van Hiele model in acquiring contemporary arts among students of the Art Department, a famous cultured intellectual with a wonderful design, targeting a community consisting of first-year students of the Art Education Department at Al-Mustansiriya University and Maysan University, through selecting a group consisting of (60) art students distributed into two equal groups (experimental and control), each group (30) students from the Art Department intentionally, and after applying the program, their agreement was measured through a tool represented by the achievement test, and the results showed that there is a statistically significant difference at the level of (0.05) between the experimental middle group and the control group in the experimental aggregate achievement test. Accordingly, the researcher concluded that the Van Hiele educational model encouraged students to participate and interact by presenting topics in a way that transitions learners from the general to the specific in terms of receiving information and knowledge. The researcher's most important recommendation is the adoption of an educational program for teaching contemporary art to first-year art education students, proposing the use of the educational program with another variable related to visual form and the method of reading visual images.